Splicing Outcomes of 5′ Splice Site GT>GC Variants That Generate Wild-Type Transcripts Differ Significantly Between Full-Length and Minigene Splicing Assays - Lin, Jin-Huan; Wu, Hao; Zou, Wen-Bin; Masson, Emmanuelle; Fichou, Yann; Le Gac, Gerald; Cooper, David N.; Férec, Claude; Liao, Zhuan; Chen, Jian-Min (Frontiers in Genetics, 2021)
Combining data derived from a meta-analysis of human disease-associated 5' splice site GT>GC (i.e., +2T>C) variants and a cell culture-based full-length gene splicing assay (FLGSA) of forward engineered +2T>C substitutions, we recently estimated that ~15-18% of +2T>C variants can generate up to 84% wild-type transcripts. Herein, we explored whether sequence context could influence the splicing outcomes of 20 +2T>C variants that generate some wild-type transcripts, in two minigene assays. We found a high discordance rate in terms of the generation of wild-type transcripts, not only between FLGSA and the minigene assays but also between the different minigene assays. In the pET01 context, all 20 wild-type minigene constructs generated the expected wild-type transcripts; of the 20 corresponding variant minigene constructs, 14 (70%) generated wild-type transcripts. In the pSPL3 context, only 18 of the 20 wild-type minigene constructs generated the expected wild-type transcripts whereas 8 of the 18 (44%) corresponding variant minigene constructs generated wild-type transcripts. Our findings emphasize the importance of sequence context in regulating splicing, raise awareness of the limitations of minigene splicing assays, and highlight the difficulties inherent in both predicting and interpreting the broad spectrum of ‘quantitative’ variants that generate a mix of both wild-type and aberrant transcripts.